Performance-Based Numerical Analysis at Various Hazard Earthquake Levels for the Retrofitting of Reinforced Concrete Frames with Reinforced Concrete Infill Walls - Georgiou, Elpida; Kyriakides, Nicholas; Chrysostomou, Christis (My University, 2023)
The performance of reinforced concrete (RC) infill walls for the seismic retrofitting of existing RC-frame buildings is evaluated at various hazard earthquake levels in this research work. The seismic retrofitting of existing multi-storey multi-bay RC frame buildings by the conversion of selected bays into new RC infill walls was studied experimentally within the SERFIN project through a series of experiments, which took place at the European Laboratory of Structural Assessment (ELSA). This was the first time that a full-scale experiment of this type of specimen was performed. This experiment aimed to study the efficiency of the retrofitting method and to examine the required amount of RC wall web reinforcement as well as the connection details between the wall and the bounding frame. To complement the experimental results and to study the interaction between the RC infills and the bounding frame both at the global and local level, a parametric study was performed by reducing the number of dowels starting from a spacing of 100 mm (monolithic) to no dowels. The parametric study was performed by nonlinear response-history analyses of a two-dimensional (2D) finite element (FE) model that was calibrated using the experimental results obtained from the full-scale experiment. The numerical results of the parametric study showed that the number of dowels used in the experimental study can be reduced significantly making the use of this method more attractive. The results from the parametric study and their analysis can lead to design recommendations. In this paper, the results from the performance-based numerical analysis are presented along with the conclusions that are drawn.
Keywords: Design Recommendations; Dowels; Earthquake Hazard Levels; Finite Element Model; Performance-Based Numerical Analysis; Retrofitting Seismic Deficient Structures